Geochemical variability and microbial metabolic functions in oligotrophic sediments exposed to minor seepage - Schnabel, Ellen; Vuillemin, Aurèle; Esser, Sarah; Griesdorn, Lea; Soares, André R.; Mørkved, Pål Tore; Jørgensen, Steffen L.; Probst, Alexander J.; Kallmeyer, Jens; , the PROSPECTOMICS Consortium (Frontiers in Microbiology, 2026)
Low primary productivity in Barents Sea surface waters and limited nutrient flux to the seafloor favor nitrification and nitrogen fixation in deep waters, resulting in a dearth of organic substrates in local sediments. The addition of labile hydrocarbons naturally occurring through seepage from subsurface reservoirs could promote microbial activity in organic-lean sediments, notably by denitrifying and sulfate-reducing microbes. Using gravity cores from an area with numerous hydrocarbon reservoirs, we document pore water geochemistry, dissolved gas concentrations, and total cell counts supplemented with taxonomic and functional marker gene analyses from metagenomes and metagenome-assembled genomes. We assess the contribution of the subsurface biosphere in producing geochemical gradients in oligotrophic sediments facing different exposure to minor seepage. In pristine seabed, i.e., not affected by hydrocarbon seepage, nitrate and ammonium profiles were consistent with denitrification down to 1 m below seafloor. By contrast, minor hydrocarbon seepage caused very different pore water profiles, which were indicative of more reducing geochemical conditions in the sediment and more advanced consumption of electron acceptors in pore water. Delivery of favorable organic substrates to anaerobic microbes through seepage was reflected in slightly higher cell densities, CH4 and CO2 concentrations, but appeared to have little impact on community diversity. This could be explained by metabolic versatility across functional guilds, with limited differentiation of sedimentary niches, favoring polyvalent fermenters at the expense of canonical denitrifiers and sulfate reducers. These versatile fermenters exhibited diverse predicted capabilities for nitrate and sulfate reduction combined with hydrocarbon degradation, (homo)acetogenesis, and nitrogen fixation. Our results further indicate that specific clades of homoacetogens (Lokiarchaeia, Bathyarchaeia, and Dehalococcoidia) could support cross-feeding interactions when fueled by simple hydrocarbons through seepage, particularly those associated with dissimilatory sulfur metabolism and fermentation of intermediate metabolites. In the absence of hydrocarbon-derived electron donors, the same clades appear capable of energy-conserving (homo)acetogenic fermentation on organic residues. Thus, we conclude that slow-growing (homo)acetogens that are ubiquitous in the marine subseafloor actively contribute to balancing biogeochemical cycles in oligotrophic sediments impacted by minor hydrocarbon seepage.